2017
DOI: 10.18632/oncotarget.19876
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis type-1 is a prognostic indicator in human gastric carcinoma

Abstract: We investigated whether the Neurofibromatosis type-1(NF1) gene was of prognostic relevance to gastric cancer (GC) patients. Immunohistochemical staining of 160 matched GC tumor and adjacent normal tissue samples showed that 58.1% (93/160) of GC samples were NF1-positive as compared to 94.4% (151/160) of normal tissue samples (χ 2 =58.05, P <0.001). qRT-PCR analysis revealed that NF1 mRNA expression is lower in GC tissues than normal tissues (χ 2 =34.23, P <0.001). Moreover, NF1 protein and mRNA levels were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Our data demonstrated that not only NF1 mRNA was decreased but also the positive rate of NF1 protein in the UPS tissue (39.71%) was significantly decreased compared with that in the adjacent normal tissue (70.59%). A research reported that 58.1% (93/160) of the gastric cancer samples were NF1-positive as compared to 94.4% (151/160) of the matched normal tissue samples ( p < 0.001) ( Liu et al, 2017 ), which was consistent with our results. In addition, the NF1 protein expression was associated with the tumor size and distant metastasis of UPS in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Our data demonstrated that not only NF1 mRNA was decreased but also the positive rate of NF1 protein in the UPS tissue (39.71%) was significantly decreased compared with that in the adjacent normal tissue (70.59%). A research reported that 58.1% (93/160) of the gastric cancer samples were NF1-positive as compared to 94.4% (151/160) of the matched normal tissue samples ( p < 0.001) ( Liu et al, 2017 ), which was consistent with our results. In addition, the NF1 protein expression was associated with the tumor size and distant metastasis of UPS in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…A molecular analysis of BRCA1/2 mutations clearly revealed distinct categories of tumours[ 23 ]. A recent study showed that NF1 has prognostic relevance to clinical outcomes in GC patients[ 24 ] and leads to the dysregulation of the RAS/MAPK pathway[ 25 ]. Our study demonstrated that PIK3CA mutations were highly frequent and occurred at the E542K and H1047R sites.…”
Section: Discussionmentioning
confidence: 99%